BrachyView: verification of LDR patient plans – hardware optimisation. (January 2019) - Brennen, T; Cutajar, D L; Alnaghy, S; Bucci, J; Bece, A; Favoino, M; Carriero, M; Lerch, M; Rosenfeld, A B; Petasseca, M
Abstract: BrachyView is a novel in-body imaging system developed with the objective to provide real-time intraoperative dosimetry for low dose rate (LDR) prostate brachytherapy treatments. Seed positions can be reconstructed after implantation by the means of a high-resolution pinhole gamma camera. The obtained dataset is then combined with conventional trans-rectal ultrasound (TRUS) imaging to locate the effective source position within the prostate volume. This study presents a comparison of two data sets containing 96 and 98 I-25 brachytherapy sources and readout by two different pin-hole collimators with 800 µm and 500 µm, respectively. This study aims to assess the effect on reconstruction of large pinholes which allow for large Field of View (FoV) and statistics of counts on the seed's projections. It was found that 100% of seeds were reconstructed by the means of the 500 µm collimator. Results from the 800 µm data showed that only 70% of seeds were reconstructed with a total 3D discrepancy of 8.20 mm in respect to CT data and an increased reconstructed position inaccuracy.